2020
DOI: 10.1039/c9fo02171j
|View full text |Cite
|
Sign up to set email alerts
|

Metagenomic analysis of gut microbiota modulatory effects of jujube (Ziziphus jujuba Mill.) polysaccharides in a colorectal cancer mouse model

Abstract: Accumulating evidence has reported that the gut microbiota could play important roles in the occurrence and progression of colorectal cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
110
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 248 publications
(112 citation statements)
references
References 49 publications
2
110
0
Order By: Relevance
“…Actinobacteria is part of the normal GM and includes beneficial genera, for example Propionibacterium , Bifidobacterium and Corynebacterium (Tian et al , 2019). Dietary L. ruthenicum , jujube polysaccharides, fibre and probiotics have been reported to promote the growth of Actinobacteria, thereby assisting in the prevention of obesity and may have potential butyric acid‐producing bacteria (Tian et al , 2019; Ji et al , 2020).…”
Section: Resultsmentioning
confidence: 99%
“…Actinobacteria is part of the normal GM and includes beneficial genera, for example Propionibacterium , Bifidobacterium and Corynebacterium (Tian et al , 2019). Dietary L. ruthenicum , jujube polysaccharides, fibre and probiotics have been reported to promote the growth of Actinobacteria, thereby assisting in the prevention of obesity and may have potential butyric acid‐producing bacteria (Tian et al , 2019; Ji et al , 2020).…”
Section: Resultsmentioning
confidence: 99%
“…In the aforementioned study, they found the level of Verrucomicrobia was increased obviously and it exhibited pro-inflammatory properties in AOM/DSS mice ( 37 ). Similarly, a reduction in the ratio of Firmicutes/Bacteroidetes had an effect on the prevention and treatment of CRC ( 40 ). Therefore, these results demonstrated that BBR partially restored the enteric microbiome community in AOM/DSS mice.…”
Section: Discussionmentioning
confidence: 99%
“…Bacteroides are important members of human intestinal microorganisms that bring countless benets to the host, devoting more than 20% of their genomes to transport and degrade polysaccharides. 58,59 Lactobacillus is a member of lactic acid-producing microorganisms that promote health. 60 Bidobacterium can generate butyrate, which provides an anti-inammatory effect.…”
Section: Diversity Of Gut Microbiota In Lps-induced Inammatory Micementioning
confidence: 99%